Search for a time- and cost-saving genetic testing strategy for maturity-onset diabetes of the young - Dusatkova, Petra; Pavlikova, Marketa; Elblova, Lenka; Larionov, Vladyslav; Vesela, Klara; Kolarova, Katerina; Sumnik, Zdenek; Lebl, Jan; Pruhova, Stepanka (Acta diabetologica, 2022)
AIMS: Correct genetic diagnosis of maturity-onset diabetes of the young (MODY) is beneficial for person's diabetes management compared to no genetic testing. Aim of the present study was a search for optimal time- and cost-saving strategies by comparing two approaches of genetic testing of participants with clinical suspicion of MODY. METHODS: A total of 121 consecutive probands referred for suspicion of MODY (Group A) were screened using targeted NGS (tNGS), while the other 112 consecutive probands (Group B) underwent a single gene test based on phenotype, and in cases of negative findings, tNGS was conducted. The study was performed in two subsequent years. The genetic results, time until reporting of the final results and financial expenses were compared between the groups. RESULTS: MODY was confirmed in 30.6% and 40.2% probands from Groups A and B, respectively; GCK-MODY was predominant (72.2% in Group A and 77.8% in Group B). The median number of days until results reporting was 184 days (IQR 122-258) in Group A and 91 days (44-174) in Group B (p < 0.00001). Mean costs per person were higher for Group A (639 ± 30 USD) than for Group B (584 ± 296 USD; p = 0.044). CONCLUSIONS: The two-step approach represented a better strategy for genetic investigation of MODY concerning time and costs compared to direct tNGS. Although a single-gene investigation clarified the diabetes aetiology in the majority of cases, tNGS could reveal rare causes of MODY and expose possible limitations of both standard genetic techniques and clinical evaluation.
Keywords: Monogenic diabetes; Diabetes Mellitus, Type 2; mutace; genetické testování; Phenotype; Genetic Testing; Humans; Mutation; Dideoxy sequencing; lidé; diabetes mellitus 2. typu; MODY; fenotyp; Targeted next generation sequencing